A Single Residue Switch for Mg(2+)-dependent Inhibition Characterizes Plant Class II Diterpene Cyclases from Primary and Secondary Metabolism - Mann, Francis M. (American Society for Biochemistry and Molecular Biology, 2010)
Class II diterpene cyclases mediate the acid-initiated cycloisomerization reaction that serves as the committed step in biosynthesis of the large class of labdane-related diterpenoid natural products, which includes the important gibberellin plant hormones. Intriguingly, these enzymes are differentially susceptible to inhibition by their Mg(2+) cofactor, with those involved in gibberellin biosynthesis being more sensitive to such inhibition than those devoted to secondary metabolism, which presumably limits flux toward the potent gibberellin phytohormones. Such inhibition has been suggested to arise from intrasteric Mg(2+) binding to the DXDD motif that cooperatively acts as the catalytic acid, whose affinity must then be modulated in some fashion. While further investigating class II diterpene cyclase catalysis, we discovered a conserved basic residue that seems to act as a counter ion to the DXDD motif, enhancing the ability of aspartic acid to carry out the requisite energetically difficult protonation of a carbon-carbon double bond and also affecting inhibitory Mg(2+) binding. Notably, this residue is conserved as a histidine in enzymes involved in gibberellin biosynthesis and as an arginine in those dedicated to secondary metabolism. Interchanging the identity of these residues is sufficient to switch the sensitivity of the parent enzyme to inhibition by Mg(2+). These striking findings indicate that this is a single residue switch for Mg(2+) inhibition, which not only supports the importance of this biochemical regulatory mechanism in limiting gibberellin biosynthesis, but the importance of its release, presumably to enable higher flux, into secondary metabolism.